Answer:
The solutions to the quadratic equations are:
![x=√(13)+3,\:x=-√(13)+3](https://img.qammunity.org/2022/formulas/mathematics/college/4v73fa2m8ndqbuuf09j0cngsa1nyti5wtq.png)
Explanation:
Given the function
![y\:=\:x^2\:-\:6x\:-\:4](https://img.qammunity.org/2022/formulas/mathematics/college/94w2lx21dwb1yle22feaf6j0pqadw1fagy.png)
substitute y = 0 in the equation to determine the zeros
![0\:=\:x^2\:-\:6x\:-\:4](https://img.qammunity.org/2022/formulas/mathematics/college/nhdt2m4hj63czpy8lhhispmwru9hcv0iz0.png)
Switch sides
![x^2-6x-4=0](https://img.qammunity.org/2022/formulas/mathematics/college/mun03kga6vw0au4gpmtk7pe9nijomvgosk.png)
Add 4 to both sides
![x^2-6x-4+4=0+4](https://img.qammunity.org/2022/formulas/mathematics/college/g1t4glvwnmguf4cbge5692gvjtzhzqgh3e.png)
Simplify
![x^2-6x=4](https://img.qammunity.org/2022/formulas/mathematics/college/rpqcnobld1dyxem5534wlsha61tyj78ddu.png)
Rewrite in the form (x+a)² = b
But, in order to rewrite in the form x²+2ax+a²
Solve for 'a'
2ax = -6x
a = -3
so add a² = (-3)² to both sides
![x^2-6x+\left(-3\right)^2=4+\left(-3\right)^2](https://img.qammunity.org/2022/formulas/mathematics/college/91iymubf666nb6tzojr231hejm19m7yox6.png)
![x^2-6x+\left(-3\right)^2=13](https://img.qammunity.org/2022/formulas/mathematics/college/81qz5d7juyl8s9hvcwlppu1l6a8iv7dhcn.png)
Apply perfect square formula: (a-b)² = a²-2ab+b²
![\left(x-3\right)^2=13](https://img.qammunity.org/2022/formulas/mathematics/college/ig1gbi76nemyuyf6w44tiddvwhd34wz6cn.png)
![\mathrm{For\:}f^2\left(x\right)=a\mathrm{\:the\:solutions\:are\:}f\left(x\right)=√(a),\:-√(a)](https://img.qammunity.org/2022/formulas/mathematics/high-school/5v6vxgu3z7338powt2jo86eqyodjr4urg2.png)
solve
![x-3=√(13)](https://img.qammunity.org/2022/formulas/mathematics/college/s02qyrouq9vo61cj2ozdrjzqj27kn4fde6.png)
Add 3 to both sides
![x-3+3=√(13)+3](https://img.qammunity.org/2022/formulas/mathematics/college/svx5r227y4qbyl8f0j8qdte9lotj67nski.png)
Simplify
![x=√(13)+3](https://img.qammunity.org/2022/formulas/mathematics/college/14eoigw0bv5ojghwasztsbc2e313ywhktr.png)
now solving
![x-3=-√(13)](https://img.qammunity.org/2022/formulas/mathematics/college/vqnsajntanyh36cptbdw5ipgw77quyxkht.png)
Add 3 to both sides
![x-3+3=-√(13)+3](https://img.qammunity.org/2022/formulas/mathematics/college/q3gu26fjmvqyswvnnocjlh0yc87o1edfwb.png)
Simplify
![x=-√(13)+3](https://img.qammunity.org/2022/formulas/mathematics/college/elfswp3mb4593vuh3zioz6yw7ovjsr4ptn.png)
Thus, the solutions to the quadratic equations are:
![x=√(13)+3,\:x=-√(13)+3](https://img.qammunity.org/2022/formulas/mathematics/college/4v73fa2m8ndqbuuf09j0cngsa1nyti5wtq.png)